Quantifying Intellectual Terrain: Islamic Jurisprudence, Ethical Discourse, and Scholarly Impact - Apriantoro, Muhamad Subhi; Faradilla, Safina; Ashfahany, Afief El; Maruf, Aminudin; Aziza, Nur Amalia (Suhuf: International Journal of Islamic Studies, 2024)
This research aims to reveal the trend and development of scientific literature about Islamic law, ethics, and its worldwide significance, spanning the years 1954 to 2023. The utilization of quantitative and network analysis enables the mapping of alterations in publication patterns, the identification of affiliations and highly productive authors, and the highlighting of journals with substantial influence. The findings indicate a significant increase in the number of published works since 1995, particularly in the early 21st century. Notably, the International Islamic University Malaysia and writers El-Seoudi, A.W.M.M. and Jadalhaq, I.M. have made considerable contributions to this surge. The examination of journals emphasizes the significant influence of "Islamic Law and Society" in the relevant literature. Furthermore, specific works like Ashraf D's publication in the "Journal of Business Ethics" in 2016 demonstrate a considerable impact in the scientific literature. Through a comprehensive examination of publication trends and influential works, the study contributes to a deeper understanding of Islamic law and ethics within academic circles. It underscores the need for interdisciplinary collaboration and engagement with diverse perspectives to grasp the complexities of Islamic jurisprudence and ethical frameworks.  In conclusion, this research provides a valuable resource for scholars, policymakers, and practitioners seeking to navigate the intricate terrain of Islamic law and ethics. By delineating trends, identifying key contributors, and highlighting influential publications, the study offers a nuanced perspective on the evolving discourse surrounding these critical subjects.